Retos para la formación de profesionales en derechos en salud. El caso de Perú - Henríquez-Suárez, Milagro (2019)
ABSTRACT Introduction: Currently the right to health is part of the fundamental human rights and is recognized internationally by the United Nations Organization. The objective of this article is to describe experiences of educational programs of health rights, and poses challenges for strengthening competencies within the framework of health rights, analyzing Peru as a specific case. Development: To ensure timely and quality health care, based on health rights, and within the framework of what is established by global regulations on human rights in health, health professionals are required to develop in a favorable environment for health practice and complementary services with appropriate resources. Health institutions must offer, in coordination with the universities and state entities, training programs on health rights considering the current legal framework and the continuous training of professionals. Conclusions: It is important to promote training for health professionals in the area of health rights at a global and local level, considering the determinants of health and the different socio-cultural environments, initiatives that should be promoted both from the academy as from the government. In the case of Peru, at the government level, it is proposed to promote it from the Ministry of Health and the National Health Superintendence, the entity in charge of protecting and promoting health rights.